2016
DOI: 10.4269/ajtmh.15-0576
|View full text |Cite
|
Sign up to set email alerts
|

Amebic Liver Abscess in Israeli Travelers: A Retrospective Study

Abstract: Abstract. Amebic liver abscess (ALA) is endemic in developing countries. The epidemiology and clinical characteristics of the disease in developing countries are well described. Travelers from nonendemic countries can serve as a model for the natural history of ALA. Currently, the available literature on travelers is limited. This is a retrospective observational study on Israeli travelers diagnosed with ALA. Data regarding travel history, clinical presentation, imaging, and treatment were collected and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, the real number of Entamoeba infected subjects who develop AHA, is unknown. AHA has been reported following travels to endemic areas for very brief periods (4 days) (Anesi & Gluckman, 2015;Lachish et al, 2016).…”
Section: Amebian Hepatic Abscessmentioning
confidence: 99%
“…However, the real number of Entamoeba infected subjects who develop AHA, is unknown. AHA has been reported following travels to endemic areas for very brief periods (4 days) (Anesi & Gluckman, 2015;Lachish et al, 2016).…”
Section: Amebian Hepatic Abscessmentioning
confidence: 99%
“…Amoebic liver abscess is the most common extraintestinal manifestation caused due to movement of amebae through the portal venous system. [ 3 ] It is clinically presented within 8–20 weeks of exposure,[ 4 ] with fever (38.5–39.5°C) and right upper quadrant pain. [ 5 ] Hepatomegaly and liver tenderness are commonly observed on physical examination, with less than 10% of cases having jaundice.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Saudi Arabia and the UK found that all patients with ALA were either from or had recently travelled to the Indian subcontinent [ 11 ]. Likewise, a study on Israeli travellers found that the vast majority of them had travelled to the Indian subcontinent before the onset of symptoms [ 17 ]. Recent data from the United Nations Department of Economic and Social Affairs indicate that migrants comprise a staggering 87.9% of UAE’s total population [ 18 ].…”
Section: Discussionmentioning
confidence: 99%